Nilai-nilai Pendidikan Islam dalam Novel Adzra’ Jakarta Karya Najib Kailani - Muhammad Sofyan; Arif Nursihah; Hamdan Hambali (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
Abstract: This research is a library research with a qualitative approach. The primary data source in this study is the novel Adzra Jakarta by Najib Kailani, while the secondary sources are various books related to the field under study. Collecting data using observation and documentation methods. Methods of data analysis using descriptive analysis methods. This study aims to determine the content of the message about what is contained in the novel Adzra Jakarta by Najib Kailani, both in the fields of aqidah, sharia, and morals. The research results in this research are that the novel Adzra Jakarta by Najib Kailani Sarat will preach messages from the fields of aqidah, sharia, and morals. Among them: Da'wah messages in the field of aqidah in the novel Adzra Jakarta include: Allah is eternal, Allah is able to save, Allah is the creator of everything, Allah is all-forgiving, faith in hell Da'wah messages in the field of sharia in the novel Adzra Jakarta, include: halal and haram, prohibition of killing, prohibition of touching the opposite sex who is not, mahram, prohibition of marrying non-Muslims, reading the Koran eliminates turmoil, prohibition of drinking khamr, methods dress a Muslim woman Da'wah messages in the field of morals in the novel Adzra Jakarta, include: arrogance, courage to convey the truth, deception / lies, morals in arguing, ukhuwah Islamiyah, zhalim, attitude of mercy, respect for older people. Abstrak: Penelitian ini adalah penelitian kepustakaan (library research) dengan pendekatan kualitatif. Sumber data primer dalam penelitian ini adalah novel Adzra Jakarta karya Najib Kailani, sedangkan sumber sekundernya adalah berbagai buku yang berkaitan dengan bidang yang diteliti. Pengumpulan data menggunakan metode observasi dan dokumentasi. Metode analisis data menggunakan metode analisis deskriptif. Penelitian ini bertujuan untuk mengetahui nilai-nilai pendidikan Islam yang terkandung dalam Novel Adzra Jakarta karya Najib Kailani, baik dalam bidang aqidah, syariah, maupun akhlak. Hasil Penelitian dalam penelitian ini yaitu bahwa novel Adzra Jakarta karya Najib Kailani Sarat akan nilai-nilai pendidikan Islam baik dari bidang aqidah, syariah, maupun akhlak. Di antaranya: Nilai pendidikan Islam dalam bidang aqidah yang ada dalam novel Adzra Jakarta meliputi: Allah maha kekal, Allah yang mampu menyelamatkan, Allah sang pencipta segala sesuatu, Allah maha pengampun, keimanan kepada neraka. Nilai pendidikan Islam dalam bidang syariah yang ada dalam novel Adzra Jakarta, meliputi: halal dan haram, larangan membunuh, larangan menyentuh lawan jenis yang bukan, mahram, larangan menikahi non-muslim, membaca al-Qur’an menghilangkan kegalauan, larangan meminum khamr, cara berpakaian seorang muslimah Nilai pendidikan Islam dalam bidang akhlak yang ada dalam novel Adzra Jakarta, meliputi: kesombongan, keberanian menyampaikan kebenaran, tipu daya/kebohongan, akhlak dalam berdebat, ukhuwah islamiyah, kezhaliman, sikap rahmah, menghormati kepada orang yang lebih tua.